Interespaços: paisagens e territórios em cenas - Helena Augusta da Silva Gomes (2023)
Image, space, gaze. These concept-words are so familiar and yet so dispersive to attempts to fit them into two-line explanations. Relating them, we can grope some of their expressions. Departing from some spatial spellings, manifested in landscapes and territories practiced, perceived and expressed in images, what animates this thesis is the idea that the contemporary documentary film can be, in addition to recording a dimension of space, a manifestation of it. It is also inspired by the idea of interspaces, made in the scene, that coexist with the filmic locations and as a new creation. Crossed by processes, practices and proposed and possible openings in the writing of each film, new instances are opened: landscapes and territories in scene. Such interspaces are studied in two essays. The first one deals with the territory and the scene in “Urihi Haromatipë – Curadores Da Terra-Floresta”, by Morzaniel Iramari, filmed among Yanomami indigenous, between 2011 and 2012; the second one focuses on the study of the landscape and the scene of the documentary “O botão de pérola”, by Chilean filmmaker Patricio Guzmán, released in 2015.